Hepatitis C in Uganda: Identification of infected blood donors for micro-elimination - Joan Nankya-Mutyoba; Betty S. Apica; Grace Otekat; Dorothy B. Kyeyune; Lourita Nakyagaba; Joletta Nabunje; Mary Nakafeero; Emmanuel Seremba; Ponsiano Ocama (Elsevier, 2021)
Background: The drive to eliminate viral hepatitis by 2030 is underway. However, locally generated data on active infection is required to focus such efforts. We performed a regionally-inclusive survey to determine prevalence of active HCV, genotypes and related factors among Ugandan blood donors. Methods: Participants from regional blood banks and blood collection centers were surveyed for information on demographic, clinical and lifestyle factors. Blood was assayed for HCV infection, HCV genotypes and subtypes. Logistic regression was performed to determine factors associated with active HCV infection. Results: Of 1243 participants, 1041 (83.7%) were male, average age (SD), 27.7 (9.8). Prevalence of active HCV infection was 7.8% and we identified 3 genotypes. Median age (adj. OR (95% CI) = 1.03 (1.01-1.06), p-value = 0.040)), Northern region of birth versus Central or Eastern (adj. OR (95% CI) = 10.25 (2.65-39.68), p-value = 0.001)), Northern residence, versus Central or Eastern (adj. OR (95% CI) = 0.23 (0.08-0.65), p-value = 0.006)), and being married (versus single/divorced) adj. OR 2.49(1.3-4.79), p-value = 0.006 were associated with active HCV infection. Conclusion: Targeted interventions in at-risk populations coupled with linkage to care and treatment will help achieve the WHO elimination goals in this setting.